Nanostructure Zinc Oxide with Cobalt Dopant by PLD for Gas Sensor Applications - A.A. Yousif; N.F. Habubi; A.A. Haidar (Журнал нано- та електронної фізики)
The present paper is based on study of polycrystalline ZnO:Co thin films deposited on glass substrates by pulsed laser deposition (PLD) technique using pulsed Nd-YAG laser with wavelength ( = 532 nm) and duration (7 ns) and energy fluence (1.4 J/cm 2) with different doping (1 wt. %, 3 wt. % and 5 wt. %). The X-Ray diffraction patterns of the films showed that the ZnO films and ZnO:Co films exhibit wurtzite crystal structure and high crystalline quality. The root mean square (RMS) surface roughness of Co doped ZnO thin films was estimated using atomic force microscopy (AFM) found to be 50.95 nm, 55.78 nm, 56.94 nm and 67.88 nm for pure,1 wt. %, 3 wt. % and 5 wt. % Co doping concentrations respectively. Through the electrical properties, electrical D.C conductivity at temperature range (27-300) ºC for ZnO:Co films as studied which are realized that these films have two activation energies. Hall effect is studied to estimate the type of carriers, from the result we deduced that the ZnO:Co thin films are n-type. The films exhibited good sensitivity to the ethanol vapors with quick response-recovery characteristics and it was found that the sensitivity for detecting (80) ppm, for ethanol vapor was of (27.5), (31.75), (79.0) and (53.1) at an operating temperature of (50) C for ZnO:Co thin films.